The Effects of Exogenous Surfactant Treatment in a Murine Model of Two-Hit Lung Injury. (February 2015) - Zambelli, Vanessa; Bellani, Giacomo; Amigoni, Maria; Grassi, Alice; Scanziani, Margherita; Farina, Francesca; Latini, Roberto; Pesenti, Antonio
<x xml:space="preserve">Abstract</x> BACKGROUND: Because pulmonary endogenous surfactant is altered during acute respiratory distress syndrome, surfactant replacement may improve clinical outcomes. However, trials of surfactant use have had mixed results. We designed this animal model of unilateral (right) lung injury to explore the effect of exogenous surfactant administered to the injured lung on inflammation in the injured and noninjured lung. METHODS: Mice underwent hydrochloric acid instillation (1.5 mL/kg) into the right bronchus and prolonged (7 hours) mechanical ventilation (25 mL/kg). After 3 hours, mice were treated with 1 mL/kg exogenous surfactant (Curosurf®) (surf group) or sterile saline (NaCl 0.9%) (vehicle group) in the injured (right) lung or did not receive any treatment (hydrochloric acid, ventilator-induced lung injury). Gas exchange, lung compliance, and bronchoalveolar inflammation (cells, albumin, and cytokines) were evaluated. After a significant analysis of variance (ANOVA) test, Tukey post hoc test was used for statistical analysis. RESULTS: At least 8 to 10 mice in each group were analyzed for each evaluated variable. Surfactant treatment significantly increased both the arterial oxygen tension to fraction of inspired oxygen ratio and respiratory system static compliance (P = 0.027 and P = 0.007, respectively, for surf group versus vehicle). Surfactant therapy increased indices of inflammation in the acid-injured lung compared with vehicle: inflammatory cells (685 [602–773] and 216 [125–305] × 1000/mL, respectively; P < 0.001) and albumin in bronchoalveolar lavage (BAL) (1442 ± 588 and 743 ± 647 μg/mL, respectively; P = 0.027). These differences were not found (P = 0.96 and P = 0.54) in the contralateral (uninjured) lung (inflammatory cells 131 [78–195] and 119 [87–149] × 1000/mL and albumin 135 ± 100 and 173 ± 115 μg/mL). CONCLUSIONS: Exogenous surfactant administration to an acid-injured right lung improved gas exchange and whole respiratory system compliance. However, markers of inflammation increased in the right (injured) lung, although this result was not found in the left (uninjured) lung. These data suggest that the mechanism by which surfactant improves lung function may involve both uninjured and injured alveoli.